THE RESPONSE OF CROSS-BORDER E-COMMERCE MERCHANTS TO DE MINIMIS THRESHOLDS IN INDONESIA - Tito Wibisono; Khoirunurrofik (Unit Penerbitan Politeknik Keuangan Negara STAN, 2023)
In four years, Indonesia has changed the de minimis threshold twice. This study aims to describe on how merchants react to tax regulations, especially international trade taxes, when conducting cross-border e-commerce transactions. By using administrative data on imported documents for shipments for the period 2017-2020, which includes the application period of the three de minimis thresholds of USD 100, USD 75 and USD 3, this study found that in each application period of the De -Minimis a bunching behavior gave threshold for exemption from import duties and taxes related to imports. This study also finds a similar phenomenon at the threshold of low-value shipments around the 1,500 value, where merchants are bunching to use simplified declarations and flat-rate pricing with faster procedures and lower costs.